Positive fitness effects help explain the broad range of Wolbachia prevalences in natural populations - Karisto, Petteri; Duplouy, Anne; de Vries, Charlotte; Kokko, Hanna (Peer Community In, 2022)
The bacterial endosymbiont Wolbachia is best known for its ability to modify its host’s reproduction by inducing cytoplasmic incompatibility (CI) to facilitate its own spread. Classical models predict either near-fixation of costly Wolbachia once the symbiont has overcome a threshold frequency (invasion barrier), or Wolbachia extinction if the barrier is not overcome. However, natural populations do not all follow this pattern: Wolbachia can also be found at low frequencies (below one half) that appear stable over time. Wolbachia is known to have pleiotropic fitness effects (beyond CI) on its hosts. Existing models typically focus on the possibility that these are negative. Here we consider the possibility that the symbiont provides direct benefits to infected females (e.g. resistance to pathogens) in addition to CI. We discuss an underappreciated feature of Wolbachia dynamics: that CI with additional fitness benefits can produce low-frequency (< 1/2) stable equilibria. Additionally, without a direct positive fitness effect, any stable equilibrium close to one half will be sensitive to perturbations, which make such equilibria unlikely to sustain in nature. The results hold for both diplodiploid and different haplodiploid versions of CI. We suggest that insect populations showing low-frequency Wolbachia infection might host CI-inducing symbiotic strains providing additional (hidden or known) benefits to their hosts, especially when classical explanations (ongoing invasion, source-sink dynamics) have been ruled out.
Keywords: endosymbionts; Wolbachia